1996
DOI: 10.1021/ma9511659
|View full text |Cite
|
Sign up to set email alerts
|

Melting Behavior of High-Temperature Polymers

Abstract: The melting behavior of three representative semirigid polymers, poly(aryl ether ether ketone), poly(ethylene terephthalate), and poly(ethylene naphthalenate), has been studied. Analysis of experimental results indicates that the melting process is morphologically the reverse of the isothermal crystallization process with respect to primary and secondary structural elements. On this basis, it is hypothesized that melting of all three polymers occurs in three distinct steps, assuming that spherulites are compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 32 publications
7
89
0
Order By: Relevance
“…It may also imply that the thickest mother lamellae (peak I) were first formed and then the branched lamellae (peak II) infill spherulites during primary crystallization. 27,32 This branched effect may be analogously reported by Medellín-Rodríguez et al 27 On the other hand, less variety of color was observed by increasing the crystallization temperature, indicating that the lamellar thickness became more homogeneous at higher T c . This result corresponds well to that of Figure 2, where the triple melting peaks evolve into one broader peak with increasing crystallization temperature.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It may also imply that the thickest mother lamellae (peak I) were first formed and then the branched lamellae (peak II) infill spherulites during primary crystallization. 27,32 This branched effect may be analogously reported by Medellín-Rodríguez et al 27 On the other hand, less variety of color was observed by increasing the crystallization temperature, indicating that the lamellar thickness became more homogeneous at higher T c . This result corresponds well to that of Figure 2, where the triple melting peaks evolve into one broader peak with increasing crystallization temperature.…”
Section: Resultssupporting
confidence: 79%
“…If we assume that the birefringence remains constant in all samples at the same thermal history, the increase in phase difference may be considered due mainly to the change in thickness. 27,30 To account for the relation between the melting temperature and the lamellar thickness, the Thomson-Gibbs equation 31 is generally used…”
Section: Resultsmentioning
confidence: 99%
“…Heisey et al 44 have determined that PEN crystallizes at a higher temperature and slower rate than PET. This is in agreement with the results reported by Rodriguez 50 who also determined that PET/PEN blends crystallized much faster than the copolymers of the same composition. Santa Cruz et al 51 have determined that in copolymers containing low levels of PEN (0-30 mol %), the crystalline structure is composed solely of PET, while the PEN remains in the amorphous phase.…”
Section: 44−49supporting
confidence: 93%
“…The multiple melting peaks oftentimes seen in neat PET have been attributed to melting/recrystallization/remelting sequences within a single heating run [37], to the development of a dual population of lamella thickness due to primary (thicker lamella) and secondary crystallization (thinner lamella) [38] or to a combination of those two contributions [39,40]. In Fig.…”
Section: Resultsmentioning
confidence: 99%